2012
DOI: 10.1155/2012/850468
|View full text |Cite
|
Sign up to set email alerts
|

Titanium Dioxide-Mediated Photcatalysed Degradation of Two Herbicide Derivatives Chloridazon and Metribuzin in Aqueous Suspensions

Abstract: The aim of this paper is to find out the optimal degradation condition for two potential environmental pollutants, chloridazon and metribuzin (herbicide derivatives), employing advanced oxidation process using TiO 2 photocatalyst in aqueous suspensions. The degradation/mineralization of the herbicide was monitored by measuring the change in pollutant concentration and depletion in TOC content as a function of time. A detailed degradation kinetics was studied under different conditions such as types of TiO 2 (a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(2 citation statements)
references
References 32 publications
(23 reference statements)
1
1
0
Order By: Relevance
“…From these results, it is sufficient to conclude that the degradtion of metribuzin by nZVI NPs occurs better in an acidic medum than basic medium. This is in agreement with several studies [15][16][17], which have reported slow degradation of most pesticides using Fe 0 with the increasing pH value of the reaction medium.…”
Section: The Effect Of Ph On the Degradation Of Metribuzinsupporting
confidence: 93%
“…From these results, it is sufficient to conclude that the degradtion of metribuzin by nZVI NPs occurs better in an acidic medum than basic medium. This is in agreement with several studies [15][16][17], which have reported slow degradation of most pesticides using Fe 0 with the increasing pH value of the reaction medium.…”
Section: The Effect Of Ph On the Degradation Of Metribuzinsupporting
confidence: 93%
“…In another study, two different photocatalysts which were TiO 2 /Al 2 O 3 /carbon nanotube nanocomposite and TiO 2 /Al 2 O 3 /graphene were utilized for photocatalytic degradation of metamifop where photodegradation percentage were 95% and above in the presence of UV light and 2 Lmin −1 of air [ 110 , 111 ]. Khan et al [ 112 ] found that TiO 2 can efficiently catalyzed the degradation and mineralization of herbicide derivatives chloridazon, and metribuzin in the presence of UV light. In another chemical treatment approach, acid-treated graphene (G-COOH) catalyst was combined with ozone-activated peroxymonosulfate, while in a different investigation, G-C 3 N 4 co-doped with phosphorus and kalium was used [ 113 ].…”
Section: Chemical Treatmentsmentioning
confidence: 99%